(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Hepatitis B (HBsAg) and C (HCV) virus are becoming a significant causative factors in the aetiology of chronic liver disease (CLD) worldwide. However, the information on the frequency of HBsAg and HCV virus co-infection in CLD is sparsely reported in Nigeria. In this study, we assessed the frequency of HBsAg and HCV co-infection in CLD. One hundred and eleven subjects aged 19 - 76 years, comprising of 76 CLD patients and 35 apparently healthy subjects without CLD were tested for both HBsAg and HCV virus antibodies using ELISA test kits. Out of the 111 subjects recruited for this study, 76 (68.5%) were CLD patients tested positive for HBsAg and 35 (31.5%) tested negative for HBsAg and served as control. Out of the 76 CLD patients that tested positive for HBsAg, 34 (44.7%) of them also tested positive for HCV, thus, having co-infection with HBV. Incidence of co-infection was highest in those aged 36 - 45 years, and greater in males than females. Among the control group, 4 (11.4%) of the subjects (3 males and 1 female) tested positive for HCV, while 31 (88.6%) subjects (20 males and 11 females) tested negative. This work has shown that the co-infection with HBV and HCV among chronic liver disease patients and the incidence of HCV is high in our locality. Also, some of the supposed apparently healthy subjects in this study tested positive for HCV, hence the need for improving the awareness of this virus. It is therefore necessary to give immunization and test for HBsAg and HCV in both rural and urban areas.